Luth Badila's Learning Time - Badila, Muhammad Lutfi; Taufiq, Wahyu (Indonesian Journal of Innovation Studies, 2024)
Learning media play a crucial role in enhancing the student learning process, with various types of media being employed to engage students and facilitate better understanding. Posters are one such medium that can significantly enhance students' attention and interest during learning sessions. However, traditional posters often lack elements that make them interactive and engaging enough to substantially impact speaking skills and teamwork. This study aims to introduce and evaluate the effectiveness of a novel learning medium, known as Luth-Badila’s Learning Time, which utilizes uniquely designed 3D posters incorporating subject materials, quizzes, and a rotating clock embedded in a robot's head to attract students' attention and improve their speaking skills and teamwork. The implementation of Luth-Badila’s Learning Time in classrooms has shown promising results, with a noticeable increase in student engagement, improved speaking skills, and enhanced teamwork. The novelty of this learning medium lies in its interactive 3D design and the integration of multiple educational elements into a single poster, which is a significant departure from traditional 2D posters. The findings suggest that incorporating such innovative and interactive learning media in educational settings can lead to better student outcomes, particularly in terms of speaking skills and collaborative abilities. This study contributes to the existing body of knowledge by providing evidence of the benefits of using advanced, interactive posters in educational contexts, thereby encouraging educators to adopt similar approaches to enhance learning experiences. Highlights: Innovative Design: Luth-Badila’s Learning Time uses 3D posters with quizzes and a rotating clock to captivate students. Improved Skills: This medium significantly boosts speaking skills and teamwork among students. Educational Impact: Interactive posters lead to higher student engagement and better learning outcomes. Keywords: 3D Poster, Learning Media, Speaking Skills, Student Engagement